A new species of Cnemaspis (Squamata: Gekkonidae) from Temburong District, Brunei Darussalam - Kurita, Takaki; Kojima, Yosuke; Nishikawa, Kanto; Grafe, T. Ulmar (Zootaxa, 2025)
A new species of sandstone-dwelling rock gecko of the genus Cnemaspis is described from Bukit Patoi, Temburong District, Brunei Darussalam. This is the first country record for the genus, expanding the known distribution of Bornean Cnemaspis and advancing our understanding of its species diversity. Molecular phylogenetic analyses using mitochondrial and nuclear DNA sequences confirm that the new species, Cnemaspis gituen sp. nov., represents a distinct evolutionary lineage, inferred to be the sister taxon of C. lagang from northeastern Sarawak. Cnemaspis gituen sp. nov. can be morphologically distinguished from all Bornean congeners by a unique combination of characters, most notably the presence of patches of aggregated tubercles on the lower flank associated with brilliant yellow spots in males. It further differs from C. lagang by having prominent trunk tuberculation (versus indistinct) and a suite of colouration differences in males (e.g., dark brown head versus grey). Unlike members of the nigridia species group, it is differentiated by its distinctive flank spots (versus faint vertical lines), fewer paravertebral tubercles (16–20 versus 23–38), and a continuous median row of slightly enlarged, keeled subcaudals (versus smooth median subcaudals). The new species is also distinguished by its small maximum SVL (50.8 mm) and 7–10 precloacal pores (in total) and unique caudal colouration in males.